PENGARUH WORKLOAD DAN SPESIALISASI AUDITOR TERHADAP KUALITAS AUDIT DENGAN KUALITAS KOMITE AUDIT SEBAGAI VARIABEL PEMODERASI - Setiawan, Liswan; Fitriany, Fitriany (Jurnal Akuntansi dan Keuangan Indonesia, 2011)
This research aims to find empirical evidence about the impact of workload and specialization of auditors on audit quality. This research will also examine whether the quality of the audit committee can strengthen or weaken impact of workload and specialization on audit quality. This research uses four measures of workload. The results of this research indicate that the workload has a negative impact on audit quality and audit committee reduces the negative impact of workload on audit quality. One regression found that specialization has a positive effect on the quality of audit but the audit committee has no role to strengthen the positive effect of specialization on audit quality. These results indicate that when the auditor is a specialist, the audit committee has no effect in improving the audit quality. The implications from this study is that accounting firm must consider the workload of their auditor. Government also need to consider rules on workload in an accounting firm to maintain audit quality. The role of audit committees also needs to be increased because it is proved can reduce the negative impact of workload to audit quality.